Про можливості інформаційних технологій під час розробки веб-застосунків - Андрєєва, А. Ю. (ХНУРЕ, 2020)
The main functions of modern web applications are determined, the most popular technologies for their construction are considered. Effective ways to create web applications have been identified and analyzed. A review of the basic principles of building web applications and the comparative characteristics of the selected technologies. Based on the analysis, it is concluded that the C # language and ASP.NET technology are used to create web applications.